RANCANG BANGUN APLIKASI BERBASIS AKUNTANSI PADA PERSEDIAAN BARANG DAGANG MENGGUNAKAN METODE FIFO - Rahayu Nugraheni Rachmawati (Jurnal Publikasi Ekonomi dan Akuntansi, 2021)
The accounting information system when presented with a reliable system will certainly produce objective information as well. One way to achieve a reliable accounting system is by utilizing information technology that is currently developing. Computerized inventory management is very beneficial for trading companies because there are sales that occur regularly or repeatedly. Similarly, in presenting a stock report where the inventory report is a record of information on stock data of a company for a period that can be used to determine the amount of the company's stock of goods. While the inventory report is used to assess business continuity and determine company profits. Aneka Jaya supermarket, which is a company engaged in trading in making stock and financial reports, still relies on Ms. Excel still needs processing first because it has to combine data from books so that leaders cannot receive reports quickly and accurately. Likewise in analyzing financial statements so that this process makes it difficult for management to make decisions quickly. For this reason, an inventory accounting information system design is made that can process goods master data, supplier master data, customer master data, purchase transaction data, sales transaction data, accounting account data and inventory data reports more effectively and have high accuracy with using a computer, with the Visual Basic programming language and MySQL database as well as in the inventory report used with the FIFO method. From the results of the program created to help reduce data input errors, financial reports and financial analysis are produced faster and effective and efficient achievements can be made